Benchmarking Australian Enabling Programs for a National Framework of Standards. - Davis, Charmaine; Cook, Chris; Syme, Suzi; Dempster, Sarah; Duffy, Lisa; Hattam, Sarah; Lambrinidis, George; Lawson, Kathy; Levy, Stuart (Student Success v.14 n.2 p.41-49 https://doi.org/10.5204/ssj.2841, 2023)
Enabling education programs in Australia assist students, who would otherwise have been excluded from higher education, to transition into undergraduate study. These programs emerged independently in response to the needs of individual universities and the varying cohorts of students they serve. The exclusion of these programs from the Australian Qualifications Framework (AQF) has meant they remain unregulated, with no national framework for standards. The development of academic standards is a dynamic, consensus driven process, and benchmarking provides a method through which academics from across institutions can work in partnership to reach shared understandings and improve and align practices. This practice report outlines the results of the first comprehensive cross-institutional benchmarking project involving nine Australian universities and demonstrates there is shared understanding of the standards of enabling programs between institutions. These findings will contribute to the establishment of national standards for enabling programs in Australia. [Author abstract]